Membidik Khilafah (Diskursus Dakwah Politik Di Indonesia) - Mas tori; Asep Maskur (Politik Islam, 2023)
Da'wah is a very great obligation. However, the implementation of Islamic da'wah often faces problems, especially when the material and activities of da'wah are included in the political realm. Therefore, da'wah themes such as sharia, daulah and caliphate are vulnerable to resistance, especially during the current era of power.  Using a qualitative descriptive approach, this study discusses the discourse of political da'wah in Indonesia. The results of the study show that: first, political da'wah is considered a threat by the state. This view is then framed by power by linking the ideas of sharia, daulah and caliphate with the narrative of radicalism. Second, theologically and historically the themes related to the caliphate are an important part of Islamic teachings. Unlike what is alleged, political Islam has historical concepts and facts that are much appreciated by historians and scholars.